Steganography and Data Loss Prevention: An overlooked risk? - Gutiérrez Cárdenas, Juan Manuel (2017)
Steganography is the art or science of hiding information into a carrier in such a way that the hidden data could not be detected at first sight. Steganography techniques have broadened their scope of action, from hiding information into picture media, to audio steganography and to the field of network steganography. All these methods entail a potential threat to the information security policies of any business; having into the data leakage threats its likely focus. In this scenario, business corporations cannot remain blind to these types of threats and should consider adequate policies and prevention techniques to avoid these risks. We have analyzed in this article the potential dangers that an organization could face in the light of these types of steganography techniques along with a review of current commercial software vendors to analyze their offers and mishaps on Data Leakage Prevention regarding steganography risks.